P2Y12 Receptors in Tumorigenesis and Metastasis - Ballerini, Patrizia; Dovizio, Melania; Bruno, Annalisa; Tacconelli, Stefania; Patrignani, Paola (Frontiers in Pharmacology, 2018)
Platelets, beyond their role in hemostasis and thrombosis, may sustain tumorigenesis and metastasis. These effects may occur via direct interaction of platelets with cancer and stromal cells and by the release of several platelet products. Platelets and tumor cells release several bioactive molecules among which a great amount of adenosine triphosphate(ATP) and adenosine diphosphate(ADP). ADP is also formed extracellularly from ATP breakdown by the ecto-nucleoside-triphosphate-diphosphohydrolases. Under ATP and ADP stimulation the purinergic P2Y1 receptor (R) initiates platelet activation followed by the ADP-P2Y12R-mediated amplification. P2Y12R stimulation amplifies also platelet response to several platelet agonists and to flow conditions, acting as a key positive feed-forward signal in intensifying platelet responses. P2Y12R represents a potential target for an anticancer therapy due to its involvement in platelet-cancer cell crosstalk. Thus, P2Y12R antagonists, including clopidogrel, ticagrelor and prasugrel, might represent potential anti-cancer agents, in addition to their role as effective antithrombotic drugs. However, further studies, in experimental animals and patients, are required before the recommendation of the use of P2Y12R antagonists in cancer prevention and progression can be made.